Sojourner Truth's America - Washington, Margaret (Book collections on Project MUSE., 2009)
This fascinating biography tells the story of nineteenth-century America through the life of one of its most magnetic and influential characters: Sojourner Truth. In an in-depth account of this amazing activist, Margaret Washington unravels Sojourner Truth's world within the broader panorama of African American slavery and the nation's most significant reform era. Organized chronologically into three distinct eras of Truth's life, Sojourner Truth's America examines the complex dynamics of the times in which she acted, beginning with the transnational contours of her spirituality and early life as a slave. Washington then highlights Truth's awakening during nineteenth-century America's progressive surge, which propelled her ascendancy as a rousing preacher and political orator despite her inability to read and write. Throughout the book, Washington explores Truth's passionate commitment to family and community, including her vision for a beloved community that extended beyond race, gender, and socioeconomic condition and embraced a common humanity. For Sojourner Truth, the significant model for such communalism was a primitive, prophetic Christianity. Illustrated with dozens of images of Truth and her contemporaries, Sojourner Truth's America provides important insights into the turbulent cultural and political climate of the age while also separating the many myths from the facts concerning this legendary American figure.